Student and teacher perceptions of an English language test for university admission: Understanding its face validity - Jackson, Sasithorn (Journal of Language and Culture, 2022)
The perception of test users should be an important consideration in creating a test because there are some issues that only test users can respond to. Furthermore, the perception that teachers have of a test is also an important consideration and it may affect their instructional practices. Therefore, the research questions were (1) to what extent do student perceptions agree with teacher perceptions of the abilities that are involved in answering test items? And (2) what types of test items create differences between student and teacher perceptions? Sixty undergraduate students, 19 high-school teachers, and 19 university teachers participated in an online questionnaire. Twenty-two of all participants responded to the follow-up interview. Findings from the questionnaire showed that students and teachers agreed that a test item did aim to assess the ability mentioned in the questionnaire but they were uncertain if the test could assess their/ students’ ability to write, speak, and communicate in English. Moreover, the interview results showed that the English GAT test had washback on students’ test preparation and high-school teachers’ teaching or/and assessment but not on university teachers. It is hoped that the results of this study will raise the awareness of those who deal with the language test, especially the communicative test, and guide them to consider the potential influence of the test’s face validity upon testing outcomes as they relate to real-world abilities.